Inconsistency of Some Consonants In English - Hasanah, Nur; Rahmadhani , Putri Rizki; Lubis , Yani (CV. Generasi Insan Rafflesia, 2023)
Many students who are new to a foreign language are confused by nature When you say words in a foreign language, they change and the pronunciation of foreign language words is different from the native or regional language of the song Student. This researcher uses library research. Data The opinion poll was conducted using a list of words that were incorrectly uttered by students during the speech “Speaking”, explaining, or making oral presentations in front of the class. This study shows the incompatibility of some heavy vowels English In general, the difference between vowel sounds is divided into two parts, namely vowels voiced consonants and voiceless consonants vowel sound). Based on the data obtained, the authors also identify differences Some letters consist of two consonants joined together. Some kind of vowel The unrelated sounds found in the data of this study are the letters c, g and y, while the combination of two consonants that do not have the same sound, the letters sh, ch, and th. The author hopes that the results of this research can be useful for all interested parties Learn about English sounds, especially vowels Incoherence, especially vocal discrepancies.